The interplay between borderline personality disorder and oxytocin: a systematic narrative review on possible contribution and treatment options - di Giacomo, Ester; Andreini, Elena; Santambrogio, Jacopo; Arcara, Alberto; Clerici, Massimo (Frontiers in Psychiatry, 2024)
Background Borderline personality disorder (BPD) is a complex mental health condition marked by instability in mood, relationships, self-image, and behavior. Individuals with BPD often struggle with intense emotions, impulsivity, and maintaining stable relationships. Oxytocin, known as the "love hormone" or "bonding hormone," plays a crucial role in social bonding, trust, empathy, and emotional regulation and its dysregulation may contribute to BPD difficulties. This systematic review aims to analyze existing literature, examining the intricate interplay and encouraging future research and treatment strategies. Methods A systematic search of Literature in PubMed, Embase and Psychinfo, without any language or time restriction, was performed until March 2024 combining thesaurus and free-search indexing terms related to “borderline personality disorder” and “oxytocin”, producing 310 results (77 in PubMed, 166 in Embase and 67 in Psychinfo). Ninety-four full texts were analyzed, and 70 articles were included in qualitative analysis. Results Oxytocin may influence attachment styles, parental behaviors, and stress responses, particularly in individuals with a history of childhood trauma. The interaction between oxytocin, genetics, early life experiences, and environmental factors contributes to the complexity of BPD. Genetic variations in the oxytocin receptor gene may influence social and emotional abilities and contribute to the development of psychopathology. Additionally, early adverse experiences, such as childhood maltreatment, can alter oxytocin functioning, impacting social cognition and emotional regulation.However, oxytocin's role in BPD treatment remains uncertain, with some studies suggesting potential benefits for specific symptoms like social threat avoidance, while others indicate adverse effects on nonverbal behavior and mentalizing. Conclusion Understanding oxytocin's role in BPD offers insights into potential therapeutic interventions. While oxytocin-based treatments may hold promise for addressing specific symptoms, further research is needed.